To Investigate the Risk of Herpes Zoster in Women With Endometriosis: A Taiwan National Population-Based Cohort Study - Hsu, Chao-Yu; Ke, Der-Shin; Lin, Cheng-Li; Kao, Chia-Hung (Frontiers in Medicine, 2021)
Background: The objective of this study is to investigate the occurrence of herpes zoster (HZ) in patients with endometriosis. Methods: This retrospective population-based cohort study was conducted using the Taiwan National Health Insurance Research Database. Between 2000 and 2012, women aged ≥20 years with newly diagnosed endometriosis were enrolled into the endometriosis group. Each patient with endometriosis was randomly matched to 4 controls according to age and index year. All the patients were traced from the index date to HZ diagnosis, loss to follow-up, death, or the end of December 2013. Results: In total, 19,147 patients with newly diagnosed endometriosis and 76,588 participants without endometriosis were enrolled. The incidence of HZ was higher in endometriosis persons (5.36 per 1,000 person-years) than in matched controls (4.43 per 1,000 person-years) (p <0.001). After adjustment for age and comorbidities, patients with endometriosis age ≤49 years (adjusted hazard ratio [aHR] = 1.17) (p <0.001) and 50-64 years (aHR = 1.27) (p <0.05) showed significantly higher risk of HZ than the corresponding controls. Among women without any comorbidities, patients with endometriosis were 1.22 times (p <0.001) more likely to have HZ occurrence than those without endometriosis Conclusion: Taiwanese women with endometriosis may have a higher rate of HZ occurrence. Endometriosis seems to be a high burden for affected women. Therefore, we suggest that clinicians should be aware of HZ occurrence among women with endometriosis, although there may be ethnic differences.